Efektivitas Pembelajaran E-Learning Menggunakan Media Zoom Pada Materi Asam Basa - Yusnia Elviska; Neti Afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2023)
The existence of the covid-19 virus made the government issue a policy regarding learning activities from home or online learning, in order to continue in getting the educational services to improve human resources. One of applications that could be used by teachers during online learning was Zoom meeting. This research aimed at seeing the effectiveness of E-learning using Zoom Media at State Senior High School 1 Kuantan Mudik. This research used descriptive quantitative research. Questionnaire of Google form technique with survey method was used for collecting the data. The effectiveness of E-learning using zoom was seen based on 4 indicators, namely 1) learning quality, 2) learning level suitability, 3) motivating effort and, 4) timing. Indicator 1 obtained that 71% was agree that learning material was well prepared, 68% was disagree that the material was delivered well, and 56% was disagree to follow that e-learning was well conducted. Indicator 2 obtained that 82% was disagree that e-learning could replace face-to-face class, 65% was disagree that the learning objectives have been achieved, 62% was disagree that the audio and video quality of the application strongly supported e-learning. Indicator 3 obtained that 66% was disagree that the internet access was good and 71% was disagree that internet connection was not constrained during e-learning. Indicator 4 obtained that 56% was agree that the lesson was well scheduled. Overall, e-learning using zoom was considered ineffective. It could be seen from the existing problems such as learning objectives that were not achieved, the material was not delivered properly, and the internet connection was not stable.